Study of Numeracy Identification in Elementary Schools Using Educational Report Cards: Implications for the Development of Problem Solving Abilities - Nurhasanah, Aan; Raharjo, Tri Joko; Sumartiningsih, Sri; Isdaryanti, Barokah (Universitas Negeri Semarang, 2024)
This research aims to determine the relationship between numeracy and the problem solving abilities of elementary school students. Numeracy data was obtained from school education reports, while problem solving abilities were obtained from the results of tests specifically designed by researchers to get a more specific picture of students' abilities. The research method used is descriptive quantitative with a correlational approach. The research population was fifth grade students in several elementary schools in Kuningan Regency. Cumulative data from education reports is analyzed to see the overall numeracy pattern in each school. The test is designed to measure a person's problem-solving abilities. The results showed that there was a significant positive correlation between numeracy and students' problem solving abilities (r = 0.869, p < 0.01 ) . Regression analysis shows that numeracy ability significantly predicts problem solving ability (β = 0.54, p < 0.05). These findings demonstrate the importance of evaluating individual numeracy to improve problem-solving skills. From these results, it can be concluded that increasing numeracy in students can significantly increase their ability to solve problems. Therefore, efforts to strengthen numeracy learning in elementary schools are very necessary to support the development of better problem solving skills in students.